Prevalence of Helminths in Wild Asian Elephant and Indian Rhinoceros in Chitwan and Bardia National Park, Nepal - Shahi, M. K.; Gairhe, K. P. (Nepalese Veterinary Journal, 2019)
The Nepalese elephant (Elephas maximus maximus) and rhinoceros (Rhinoceros unicornis), are an important part of Nepal’s heritage, culture and wildlife conservation. Despite its importance, not much is known about the helminth parasites that affect elephant and rhinoceros. This study investigates the prevalence of helminth parasites in wild Asian Elephant and wild Indian Rhinoceros.A study was conducted from November 2011 to April 2012 to screen helminth parasites of wild asian elephant and wild Indian Rhinoceros at Chitwan and Bardia National Park of Nepal. Total of 80 samples, 40 each taken from the Wild Asian Elephants and Indian Rhinoceros. The study showed 88.75% overall prevalence of helminthes. The prevalence in Wild Asian Elephant and Indian Rhinoceros was 95% and 82.5% respectively. 97.37% and 72.73% infection were mixed infections in elephant and rhinoceros respectively.Among 38 positive samples of the elephant of CNP and BNP, 9 different types of helminth eggs were found. 15 (39.47%) were positive for Fasciola Spp. With 450 EPG count, 11 (28.95%) for Paramphistomum spp. with 600 EPG, 27 (71.05%) for Schistosoma spp. with 500 EPG, 3 (7.89%) for Dicrocoelium spp. with 900 EPG, 12 (30.16%) for Moniezia spp. with 433.3 EPG, 17 (44.74%) for Oesophagostomum spp. with 1025 EPG, 10 (26.31%) for Chabartia spp. with 1141.65 EPG, 17 (44.74) for Strongyloides spp. with 15558.335 EPG and 23 (60.53%) for Strongylus spp. with 1700 EPG.Similarly out of the 33 positive samples of Rhinoceros of CNP and BNP, 8 different types of helminth eggs were found. 11 (33.33%) were positive for Fasciola Spp. With 558.34 EPG, 10 (30.30%) for Paramphistomum spp. with 525 EPG, 7 (21.21%) for Schistosoma spp. with 475 EPG, 4 (12.12%) for Moniezia spp. with 650 EPG, 6 (18.18%) for Strongyloides spp. with 1466.67 EPG, 4 (12.12%) for Strongylus spp. with 1625 EPG, 9 (27.27%) for Toxocara spp. with 699.98 EPG and 20 (60.61%) for Trychostrongylus spp. with 1149.98 were found to be positive.